EMPOWERING THE HUMAN RESOURCES (English Learning Strategy in Mangrove Batik Small and Medium Enterprise, Wonorejo- Surabaya) - Elli Setiyo Wahyuni (Aplikasi Administrasi: Media Analisa Masalah Administrasi, 2018)
Contextual teaching and Learning (CTL) is one of english learning strategy which is appropriate to all situation. The human resources in mangrove batik small and medium enterprise are given an english practice that is valuabe for the future development of human knowledge, organization, and product market. Mangrove batik is a unique product which should be promoted internationally. In order to improve the human resources, learning english in spoken form is very important to support the basic communication in real situation and the development of mangrove batik smalland medium enterprise production.